cis–trans Isomerization of silybins A and B - Michaela Novotná; Radek Gažák; David Biedermann; Florent Di Meo; Petr Marhol; Marek Kuzma; Lucie Bednárová; Kateřina Fuksová; Patrick Trouillas; Vladimír Křen (Beilstein Journal of Organic Chemistry, 2014)
Methods were developed and optimized for the preparation of the 2,3-cis- and the 10,11-cis-isomers of silybin by the Lewis acid catalyzed (BF3∙OEt2) isomerization of silybins A (1a) and B (1b) (trans-isomers). The absolute configuration of all optically pure compounds was determined by using NMR and comparing their electronic circular dichroism data with model compounds of known absolute configurations. Mechanisms for cis–trans-isomerization of silybin are proposed and supported by quantum mechanical calculations.